Problem-Based Learning in Digital Learning Environments: A Systematic Literature Review Supporting SDG 4 - Alhusni, Hanan Zaki; Prahani, Binar Kurnia; Jatmiko, Budi; Hamiyda, Salma Hasna (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to analyze the development and implementation of Problem-Based Learning (PBL) in digital learning environments to support sustainable digital education and improve learning quality. The study focuses on identifying research trends, technologies used, and the impact of technology-supported PBL on learning outcomes. Method: This research employed a Systematic Literature Review (SLR) approach to synthesize relevant studies published between 2021 and 2025. Articles were collected from several academic databases, including Scopus, Web of Science, ScienceDirect, and Google Scholar. The selection process followed the PRISMA framework, which includes identification, screening, eligibility assessment, and inclusion. Based on the established inclusion criteria related to PBL and digital learning environments, 15 articles were selected for further analysis. The selected studies were examined to identify research trends, technological approaches, and reported learning outcomes. Result: The findings show that the integration of PBL with digital technologies has been widely implemented in various educational contexts. Digital platforms such as learning management systems, collaborative tools, and interactive digital resources support the implementation of PBL and enhance student engagement. The results indicate that technology-supported PBL improves critical thinking, problem-solving skills, and collaborative learning experiences. In addition, digital learning environments encourage more interactive and student-centered learning through discussion, exploration, and problem-solving activities. Novelty: This study provides a synthesis of recent research on PBL in digital learning environments and highlights its potential to support innovative digital learning practices. The findings also indicate that the integration of PBL and digital technologies can contribute to improving educational quality and supporting the achievement of Sustainable Development Goal 4 (Quality Education).